2019
DOI: 10.1016/j.jngse.2019.102900
|View full text |Cite
|
Sign up to set email alerts
|

Incipient motion behavior of the settled particles in supercritical CO2

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Additionally, the slippage between the particles and the carrying CO 2 can be eliminated by increasing the flow rate of the slurry (Hou et al, 2017b). Restarting the movement of particles in CO 2 is even easier than in water due to the absence of interfacial tension and the generation of additional Magnus force through high-speed spinning, facilitating the restarting process (Hou et al, 2019).…”
Section: Frontiers In Energy Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the slippage between the particles and the carrying CO 2 can be eliminated by increasing the flow rate of the slurry (Hou et al, 2017b). Restarting the movement of particles in CO 2 is even easier than in water due to the absence of interfacial tension and the generation of additional Magnus force through high-speed spinning, facilitating the restarting process (Hou et al, 2019).…”
Section: Frontiers In Energy Researchmentioning
confidence: 99%
“…Firstly, the proppant usually settles down rapidly in low-viscosity fluids (CO 2 and slickwater). The horizontal transport distance of the proppant before its settlement reduces under a low pump rate condition due to the lower horizontal dragging force (Hou et al, 2017b;Hou et al, 2019). This significantly constrains the proppant transport capability of supercritical CO 2 , and then the scale of proppant injection in fields (Table 3).…”
Section: Gap Between Theory and Practicementioning
confidence: 99%
“…1 a) and fracture level (Fig. 1 b), including the particle settling velocity (Gadde et al, 2004;Mack et al, 2014;McCabe et al, 1993;Richardson and Zaki, 1954;Yew and Weng, 2014), the critical velocity to restart the settled proppant (also used as the critical turning velocity in complex fractures) (Cao et al, 2006;Hou, Jiang, Li, Zeng andCheng, 2017a, 2017b;Hou, Jiang, Liu, et al, 2017a, 2017bRakshit Sahai, Miskimins, & Olson, 2014), the flowing layer height (H 1 ) (Hou et al, 2019a(Hou et al, , 2019bNovotny, 1977;Patankar et al, 2002;Jing Wang, Joseph, Patankar, Conway and Barree, 2003) and the equilibrium dune level (EDLthe dune height divided by fracture height) (Alotaibi and Miskimins, 2019). Based on the field pumping schedules, those features are further calculated by employing the Velocity, Settling, Bi-power, and EDL models to yield a group of independent variables, which is one of the inputs for ML models (Table 2).…”
Section: Features For Proppant Transportmentioning
confidence: 99%
“…The particle movements could reflect the proppant transporting by evaluating the ratio between particle and fluid velocities (Hou, Jiang, Li, et al, 2017a, 2017b. The Velocity model is defined as { The proppant is tending to form an equilibrium dune in low-viscosity fluids under constant injection conditions (Hou et al, 2019a(Hou et al, , 2019b, as shown in Fig. 1 (b).…”
Section: Appendix B Summary Of Feature Calculations 1 Velocity Modelmentioning
confidence: 99%
“…acting on the particle (Hou et al 2015, Liangchuan, Zaiming andZhengsong 2011). (II) The enhanced driving force (Magnus force generated by particle spin) and reduced resistance force (non-cohesive-force due to the non-interfacial-tension characteristic) results in easier restarting of the particles in Sc-CO 2 with an averaged Shields number of 0.0028 (Table 2)identifying a reduced drag force required to drive particle restarting in Sc-CO 2 (Hou et al 2019). (III) The measured particle velocity in the flowing direction reaches ~90% of the averaged fluid flow velocity under high flow-rate condition, demonstrating the high particle transport capability of Sc-CO 2 (Hou et al 2016, Hou et al 2017b).…”
Section: Particle Movements In Sc-co 2 Fracturingmentioning
confidence: 99%